The ebb and flow of the relationship between the institutional and authority of the directorate general of immigration and the directorate of general legal administration - Ismoyo, Ibnu (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
Since the beginning of independence, the authority to handle citizenship in Indonesia has experienced dynamics closely related to the scope of duties and functions of immigration. This study analyses the institutional relationship and authority between the Directorate General of Immigration and the Directorate General of AHU in handling citizenship in Indonesia. The research method used in this article is normative legal research, or doctrinal legal research. Interview techniques support the exploration of thoughts, views, and opinions related to the research topic. The results of the study indicate that the authority to handle citizenship is always closely related to the duties and functions of immigration, so that the roles of the Directorate General of General Legal Administration (Ditjen AHU) and the Directorate General of Immigration cannot be separated, even though they are administratively separate. However, the institutional relationship between these two institutions continues to face challenges, including weak coordination, overlapping authority, and inefficiencies exacerbated by their placement under different ministries. These issues have led to low operational effectiveness, poor oversight, and unsatisfactory public service delivery, as evidenced by numerous complaints about procedural clarity and fairness. Addressing these challenges requires strong leadership commitment to foster synergy and minimise sectoral interests, with regulatory reform a crucial step toward integrating administrative and field oversight functions for more efficient, accountable, and citizen-oriented management of civic affairs.